Management of a hospital outbreak of extensively drug-resistant Acinetobacter baumannii using a multimodal intervention including daily chlorhexidine baths. Issue 1 (May 2016) - Gray, A.P.; Allard, R.; Paré, R.; Tannenbaum, T.; Lefebvre, B.; Lévesque, S.; Mulvey, M.; Maalouf, L.; Perna, S.; Longtin, Y.
Summary: Background: Extensively drug-resistant Acinetobacter baumannii (XDR-Ab) is an increasingly important cause of healthcare-associated infection. Uncertainties remain concerning optimal control measures for healthcare-associated outbreaks. Aim: To describe the epidemiology and control of an XDR-Ab outbreak that involved multiple units of a large hospital from March 2012 to January 2014. Methods: Case-finding included screening of rectum, groin, throat, nose, wounds, iatrogenic portals of entry, and catheterized sites. Antimicrobial susceptibility was evaluated by disc diffusion and E-test. Resistance genes were detected by polymerase chain reaction. Clonality was assessed by pulsed-field gel electrophoresis. Charts of cases were reviewed to identify risk factors for invasive infection. Control measures included isolation and cohorting of cases, hand hygiene reinforcement, environmental decontamination, and source control with daily baths using wipes pre-impregnated with chlorhexidine gluconate. Findings: A single clonal strain of XDR-Ab colonized or infected 29 patients. Five patients died of XDR-Ab bacteraemia. Transmission occurred primarily on two wards. Colonization was detected at all anatomical screening sites; only 57% (16/28) of cases were rectal carriers. Advanced malignancy was a risk factor for bacteraemia (relative risk: 5.8; 95% confidence interval: 1.2–27.0). Transmission ended following implementation of the multimodal control strategy. No additional nosocomial cases occurred during the following 20 months. Conclusion: Our study highlights the need to screen multiple anatomic sites to diagnose carriage and identifies risk factors for XDR-Ab bacteraemia. A multimodal intervention that included daily chlorhexidine baths for cases was rapidly followed by the termination of the outbreak. Hospitals should consider similar interventions when managing future XDR-Ab outbreaks.